2009
DOI: 10.1080/00343400802154565
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Employability and Labour Under-utilization in Non-Metropolitan Labour Markets

Abstract: Baum S., Bill A. and Mitchell W. F. Employability and labour under-utilization in non-metropolitan labour markets, Regional Studies. This paper addresses labour under-utilization and considers the factors that are associated with under-utilization risk of individuals embedded in diverse non-metropolitan labour market regions. Taking survey and census data for Australian non-metropolitan regions, this paper applies a broad employability framework that presents the risk of under-utilization as a function of indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
1
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 33 publications
1
1
0
Order By: Relevance
“…As shown in other studies (Baum and Mitchell, 2010;Baum et al, 2009;Van Ham et al, 2001, inter alia), the estimates obtained in this work underscore the relevance of local job market conditions to explaining the occupational status of individuals. As a result, men and women living in provinces with higher rates of unemployment will have a lower probability of finding adequate employment and a higher probability of being unemployed.…”
Section: Estimation Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…As shown in other studies (Baum and Mitchell, 2010;Baum et al, 2009;Van Ham et al, 2001, inter alia), the estimates obtained in this work underscore the relevance of local job market conditions to explaining the occupational status of individuals. As a result, men and women living in provinces with higher rates of unemployment will have a lower probability of finding adequate employment and a higher probability of being unemployed.…”
Section: Estimation Resultssupporting
confidence: 83%
“…For example, by using multinomial logit regression models, De Jong and Madamba (2001), Leppel and Clain (1993) and Wilkins (2006) found similarities in the characteristics of unemployment and underemployment (level of education, being young and belonging to an ethnic minority). Baum et al ( , 2009 showed that the level of underemployment is determined by personal characteristics and by conditions in the local job market. Similarly, the results obtained by De Anda and Sobczak (2011), when comparing the factors for three forms of marginal employment among Caucasian and Mexican women, underscore how personal characteristics and the place of employment (industry and occupation) influence the probability of underemployment, as evidenced by the differences between the two ethnic groups.…”
Section: Background and Econometric Modelmentioning
confidence: 99%
“…Those who have given up looking for work. This includes those on government funded employment programmes ( 4 , 5 ). Australian government is aiming for inclusive employment for all ages, that is to broaden opportunities, eliminate discriminatory practices, and address structural underutilization.…”
Section: Introductionmentioning
confidence: 99%
“…Those who have given up looking for work. This includes those on government funded employment programmes (4,5). Australian government is aiming for inclusive employment for all ages, that is to broaden opportunities, eliminate discriminatory practices, and address structural underutilization.…”
Section: Introductionmentioning
confidence: 99%